Luminescent bacterial testing for monitoring hydrocarbon bioremediation – a review - Zahaba, Maryam (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
Human activities in a large array of industrial and agricultural sectors produce chemical contaminants which are chiefly hydrocarbons of various types that are potentially toxic and carcinogenic to aquatic and terrestrial organisms. Globally, millions of tons of these pollutants are generated annually, and in some areas, they are released indiscriminately to the environment. In order to overcome this problem, microbiological decontamination or bioremediation has been suggested. Bioremediation has been argued to be an efficient, economic, and adaptable alternative to physicochemical remediation. However, to date, such claims of successful bioremediation are often not supported by evidence from toxicity studies. In this regard, luminescent bacteria have been employed in some hydrocarbon remediation experiments to denote reduction in toxicity. In this review, the utilization of luminescence bacteria as toxicity monitoring agent for hydrocarbon remediation is discussed.